Bibliometric Analysis on Oil Palm, Food Security, and Bioenergy - Judijanto, Loso (Westscience Press, 2025)
This study presents a bibliometric analysis of global research on oil palm, food security, and bioenergy, aiming to map the intellectual structure, thematic evolution, and collaboration networks in this multidisciplinary domain. Using data from the Scopus database (2000–2024) and analyzed through VOSviewer, the study identifies key trends, influential authors, and emerging research themes. The results reveal that early research predominantly focused on the role of palm oil in biodiesel and biofuel production, while recent studies increasingly emphasize environmental sustainability, waste-to-energy technologies, and circular economy principles. Core keywords such as palm oil, bioenergy, and biodiesel remain central, with newer themes like anaerobic digestion and greenhouse gas gaining momentum. Malaysia leads in publication output and collaboration intensity, followed by the United States and the Netherlands. Despite robust growth in bioenergy-related research, the food security dimension remains underexplored. The study highlights the need for more integrated, socially inclusive, and geographically diverse research to support sustainable palm oil systems in the context of global food–energy–land challenges.